Frolicking within the insect realm - Mohd Tahir, Osman (Universiti Putra Malaysia Press, 2013)
For millions of years the organisms and the ecosystem have been the integral element of the world. It has evolved and gradually emerges together as an Ecosphere. The insect realm is part of the overall processes and system. This six-legged animal is among the most diverse group on the planet and represents more than half of all known living organisms. It can be found in almost all environments.